Analysis of independent active alert village in tridadi village, Sleman, D.I. Yogyakarta province - Ferry Hendra Surya; Sunarto Sunarto (Faculty of Medicine, Universitas Islam Indonesia, 2016)
Background : Active Alert Village Program has been started since 2006. The program was revitalized in order to accelerate the achievement of the Active Alert village in 2015. Its legal basis is the Decree of the Minister of Health No. 1529/Menkes/SK/X /2010 on General Guidelines for Development of Active Alert Villages. A study to evaluate this activity is needed. Objective : To determine the implementation and development of independent Active Alert Village in Tridadi Village, Sleman, DI Yogyakarta. Methods : This study was a descriptive study using case study design with qualitative analysis. Informants were determined by purposive method. Data collection was done using triangulation, which included non-participatory observation, in depth interview, as well as data and documentation of the alert village. Results : The implementation of active alert village in Tridadi had reached the stage of independence, where eight indicators of active alert village criterias had been met. This is due to the active participation of the village government, health cadres, social organizations, community leaders, and especially local residents themselves. Conclusion : Active alert village program in Tridadi has been implemented independently.